Fatal Cajun festival - Byron, Ellen (Byron, Ellen. Cajun country mystery., 2019)
Grab your tickets for Cajun Country Live!, the pickers' and crooners' answer to the legendary New Orleans Jazz and Heritage Festival. Maggie Crozat, proprietor of the Crozat Plantation B&B, plans to be in the cheering section when her friend Gaynell Bourgeois takes the stage with her band, Gaynell and the Gator Girls. The festival's headliner, native daughter Tammy Barker, rocketed to stardom on a TV singing competition. She has the voice of an angel...and the personality of a devilish diva. But Maggie learns that this tiny terror carries a grudge against Gaynell. She's already sabotaged the Gator Girls' JazzFest audition. When a member of Tammy's entourage is murdered at the festival, Tammy makes sure Gaynell is number one on the suspect list. Gaynell has plenty of company on that list--including every one of Tammy's musicians. Posing as a groupie, Maggie infiltrates Tammy's band and will have to hit all the right notes to clear her friend's name.